Analysis and research of professional competencies model of sales managers - A. O. Sanaev (Путеводитель предпринимателя)
The author emphasizes in the article an importance of implementation of the professional competencies model in commercial firm, its influence onto the work efficiency and success. There are example and technique for creation of professional competencies model for key jobs in commercial firm.